Law Enforcement in Islam - Djawahir Hejazziey (AHKAM : Jurnal Ilmu Syariah, 2015)
This article explains that the theory of Lawrence Friedman, known as the Three Elements of the legal system in law enforcement there is a significant short age, when compared with the theory contained in the Qurân, where it is explained that law enforcement should be no element of awareness of society itself, as enshrined in the story of Prophet Ibrahim and Ismail. To uphold justice not only includes three elements or pillars, but also the equally important need to incorporate elements of the law society or the legal awareness of the society itself. Law enforcement will not be performing well, if the suspect does not have the awareness of the importance of justice as law and crown law purposes DOI: 10.15408/ajis.v15i1.2843